Delineation of geologic contacts by seismic refraction with application to the fault zone between the Thompson nickel belt and the Churchill Tectonic Province - Green, A. G. (Canadian Journal of Earth Sciences, 1980)
Refracted P-wave and S-wave arrivals are studied from a fourfold multicoverage seismic experiment that has been conducted across a region that spans the contact between the Thompson nickel belt and the Churchill Province in northern Manitoba. A new technique for the calculation of accurate delay times and basement velocities for unreversed multicoverage data is introduced. In this technique, the times of rays between selected shots and receivers are combined to give initial delay time corrections and a subsequent iterative least-squares analysis yields the final delay time corrections and estimates of the basement P-wave velocities. The P-wave velocities correlate well with the basement geology and have been used to refine the location of the contact between the Moak Lake gneisses of the Thompson nickel belt and the Kisseynew gneisses of the Churchill Province. From the P-wave velocities and S-wave attenuation it is concluded that this contact is a fault zone.